Association of workplace social capital with psychological distress: results from a longitudinal multilevel analysis of the J-HOPE Study. Issue 12 (22nd December 2018) - Eguchi, Hisashi; Tsutsumi, Akizumi; Inoue, Akiomi; Hikichi, Hiroyuki; Kawachi, Ichiro
Abstract : Objectives: Workplace social capital (WSC) is increasingly recognised as a social contextual determinant of workers' mental health, but longitudinal data are sparse. We aimed to evaluate the impact of changes in unit-level WSC on psychological distress among Japanese employees using a prospective multilevel repeated-measures design. Participants and study design: We conducted a 2-year prospective cohort study with 1, 944 men and 786 women aged 18–65 years. Participants worked at two manufacturing worksites in Japan and were free from mental illness from the first to third study waves. We used a three-level multilevel regression design to evaluate the prospective association of unit-level WSC with individual-level psychological distress. WSC was measured using a validated six-item instrument and individual-level psychological distress with the Kessler Psychological Distress Scale (K6). Results: The null model indicated a significant degree of between-work unit variation in psychological distress (intraclass correlation=0.1%, p<0.001). In the full model, each SD increase in unit-level WSC was associated with 0.69 point improvement in K6 scores (95% CI −1.12 to −0.26). Conclusions: This prospective study builds on existing knowledge by showing an association between unit-level WSC and modest improvements in mental health among employees in Japan. We recommend that WSC is considered alongside other contextual influences when assessing employees' mental health risks.